Práticas discursivas de regulamentação e liberdade no processo de desenvolvimento profissional: a constituição de subjetividades de professores na Revista Nova Escola - Moura, Carmen Brunelli de (2010)
This present thesis has the object to study the discursive constitution the teacher s subjectivities of practice permeating the sections of the magazine Nova Escola between the years 2000-2005. Problematizes how the teacher s subjectivities are produced facing the discourse of truth, which effects establishes a program for autonomist professional development in a perspective of neo-liberal governmentality. Then from this uneasiness arises some requisite questions: in the new century how teacher s subjectivities are discursively produced in magazine s sections Nova Escola during those five years of governmentality? In which perspective the discourses throughout government documents in related with professional development reflect in the linguistic-discursive repertories adopted by Nova Escola? How the experts belonging to the cadre from and/or guests from the magazine, seeking equip discursive the teacher s subjectivities for the XXI Century? Therefore, this paper objective is to examine the linguistics strategies used to produce these subjectivities at magazine s sections, what it admittedly teaches another method how to be teacher; and also it analyzes the discursive practices that compound and set boundaries to the autonomist professional development proposed by sections the magazine; describe technologies used by experts to equip and conduct of conduct the teacher to govern the self. This research is inserted theoretically in the field of Applied Linguistis, to the Cultural Studies and about the contribution of Michel Foucault s theories and methodologically in the perspective discursive interpretative. The results seek to show that the teacher s subjectivities are produced by many technologies of the self, traversed by government discourses and ratified by discursive practices of the magazine s experts. That discourse, without any oppressing or authoritarian connotation, opens space for practice of Freedom and self guiding to both constitute the subjectivity process of the teacher in the XXI Century s path